2019
DOI: 10.3389/fmicb.2019.01855
|View full text |Cite
|
Sign up to set email alerts
|

A Model Based on the Combination of IFN-γ, IP-10, Ferritin and 25-Hydroxyvitamin D for Discriminating Latent From Active Tuberculosis in Children

Abstract: In recent years, pediatric research on tuberculosis (TB) has focused on addressing new biomarkers with the potential to be used as immunological non-sputum-based methods for the diagnosis of TB in children. The aim of this study was to characterize a set of cytokines and a series of individual factors (ferritin, 25-hydroxyvitamin D [25(OH)D], parasite infections, and nutritional status) to assess different patterns for discriminating between active TB and latent TB infection (LTBI) in children. The levels of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…It is well known that neither TST nor IGRAs can distinguish between LTBI and active cases 21,22 . In our experience 23 , a model based on the combination of IFN-γ, IP-10, ferritin and 25-hydroxyvitamin D could improve the detection of patients with subclinical TB. The metabolomic approach we described may be useful in detecting the early stages of the disease.…”
Section: Discussionmentioning
confidence: 95%
“…It is well known that neither TST nor IGRAs can distinguish between LTBI and active cases 21,22 . In our experience 23 , a model based on the combination of IFN-γ, IP-10, ferritin and 25-hydroxyvitamin D could improve the detection of patients with subclinical TB. The metabolomic approach we described may be useful in detecting the early stages of the disease.…”
Section: Discussionmentioning
confidence: 95%
“…Monitoring inflammatory status may be useful to predict anti-TB treatment outcomes and combining different immunological biomarkers could increase the predicting accuracy of treatment outcome [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The serum biosignature consisting of 16 proteins (APRIL/TNFSF13, sCD30/TNFRSF8, chitinase 3-like 1, sIL-6Rα, IL-8, IL-11, IL-12(p70), IL-19, IL-28A/IFN-λ2, LIGHT/TNFSF14, MMP-1, MMP-2, MMP-3, OPN, PTX-3, TWEAK/TNFSF12) was found informative for the differentiation between the TB and HC groups, while the panel of 15 proteins (IL-6, APRIL/TNFSF13, sCD30/TNFRSF8, gp130/sIL-6β, IL-2, sIL-6Rα, IL-8, IL-29/IFNλ1, IL-35, MMP-2, MMP-3, OPN, PTX-3, sTNF-R2, TWEAK/TNFSF12) distinguished the HC group from the LTBI cohort. Currently, a number of studies have demonstrated a potential of blood-derived host protein biomarkers in the diagnosis of active TB [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. A 6-marker serum protein biosignature consisting of CRP (c-reactive protein), IFN-γ, IP-10 (human interferon-inducible protein 10), CFH (complement factor H), Apo-AI (apolipoprotein AI), and SAA (serum amyloid A) showed a potential in the diagnosis of childhood tuberculous meningitis48.…”
Section: Discussionmentioning
confidence: 99%
“…It follows from the literature data that different models based on the combination of immune mediators, measured either in serum or M.tb -stimulated cultures, achieved diagnostic performance to discriminate between active and latent pulmonary TB in children. Chegou et al reported that the measurement of the levels of IFN-α2, IL-1Ra, sCD40L, and VEGF (vascular endothelial growth factor) might be a useful method for differentiating between active TB disease and latent M.tb infection, while other authors found the same utility for IFN-γ, IP-10, ferritin, and 25-hydroxyvitamin D [ 50 , 51 ]. Another six-cytokine signature for detecting TB infection and discriminating active from latent TB included M.tb antigen-stimulated levels of IFN-γ, IP-10, and IL-Ra, and unstimulated levels of IP-10, VEGF, and IL-12(p70) [ 52 ].…”
Section: Discussionmentioning
confidence: 99%